Species of the Genus Idiomacromerus (Hymenoptera, Chalcidoidea, Torymidae) Reared from Flower Heads of Some Asteraceae in Israel - Zerova, M.D.; Seryogina, L.Ya.; Kuslitzky, W.S.; Argov, Ya. (Вестник зоологии, 2013)
Four species of the genus Idiomacromerus Crawford, 1914 are recorded from Israel as reared from flower heads of Centaurea spp. (Asteraceae). Two of them, Idiomacromerus artusis Zerova, sp. n. and I. persimilis Zerova, sp. n. are described. Четыре вида рода Idiomacromerus Crawford, 1914 отмечены из Израиля как выведенные из соцветий Centaurea spp. (Asteraceae). Описаны два вида: Idiomacromerus artusis Zerova, sp. n. и I. persimilis Zerova, sp. n.